Perlindungan Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Narkotika Pada Tingkat Penyidikan Di POLRES Klaten - Sholeh Rohmadi; Burham Pranawa; Ananda Megha Wiedhar Saputri (Jurnal Bedah Hukum, 2021)
Indonesia is a developing country where all aspects are progressing quite rapidly. On the one hand, the impact of the influence of progress both in science, technology, cultural progress and development developments in general has an impact on all human life (society), including children. committed by children, one of which is drug abuse. The purpose of this study was to determine the legal protection of children as perpetrators of narcotics crimes in the City of Klaten and to find out the obstacles in the process of investigating children as perpetrators of narcotics crimes atythe Klaten Police. This study uses the Juridical Empirical method by combining primary data obtained from the field and secondary data from written legal materials and legislation relating to the problems that will be discussed in writing this thesis. Legal protection of children as perpetrators of narcotics crimes at the investigation level by the Klaten Resort Police starting from the arrest, detention, examination carried out in accordance with the Child Criminal Justice System Act. Children who are in conflict with the law, especially narcotics crimes at the Klaten Police, always prioritize diversion efforts if the diversion requirements are met. Legal protection for children as perpetrators of narcotics crimes at the investigation level can be realized through the role of law enforcement, namely the Klaten Resort Police. The obstacles in the investigation process by the Klaten Police are internal factors and external factors. Internal factors are the absence of special investigators for children and lack of time to arrest, while external factors are calling the child's parents sometimes unable to attend to accompany, the actions of the child himself, legal advisors, lack of public awareness. namely the need for government socialization about the dangers of narcotics abuse and the need to increase the ability of police personnel by providing special professional training.